Entomopathogenic Nematology. - Gaugler, R. (CAB International, 2001)
This text provides a comprehensive review of entomopathogenic nematology. It reviews fundamental biology; setting a taxonomic foundation for nematodes and their bacterial processes involved in parasitism and to nematode ecology, and describes technological advances and control methodologies.